2005
DOI: 10.1021/ac051701n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Adsorption to LiMo3Se3 Nanowire Film Chemiresistors

Abstract: Thin films of metallic nanowire bundles derived from the Chevrel compound LiMo3Se3 undergo reversible increases of their electrical resistance (up to 70%) upon exposure to vapors of organic solvents (Qi, X. B.; Osterloh, F. E. J. Am. Chem. Soc. 2005, 127 (21), 7666-7667). Using quartz crystal microbalance measurements with four analytes, we demonstrate here that the temporal and steady-state resistance changes of the films depend on the time following the adsorption and on the number of molecules that adsorb t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The orange lines on the STEM image outline one bundle (on the right-hand side of the image) that splays out and joins up with other nanowires on the left-hand side of the image. The bright spots seen in the image are due to solvent residue . Figures b and c are STEM images of LiMo 3 Se 3 nanowire bundles with splayed ends, typical of the constituent materials of these networks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The orange lines on the STEM image outline one bundle (on the right-hand side of the image) that splays out and joins up with other nanowires on the left-hand side of the image. The bright spots seen in the image are due to solvent residue . Figures b and c are STEM images of LiMo 3 Se 3 nanowire bundles with splayed ends, typical of the constituent materials of these networks.…”
Section: Resultsmentioning
confidence: 99%
“…It is easy to understand how a network of this type is formed by directed self-assembly, particularly in the context of the pronounced bonding anisotropy that exists within the solid crystal. A strong end-to-end interaction between the building-blocks guarantees strong ordering along the wire direction and ultimately the growth of long highly ordered wires that are responsible for the excellent conductivity of these films. ,,, On the other hand, the lateral interaction between building blocks is rather weak, leading to variable interwire spacing in a bundle and which in turn facilitates the interweaving of wires from one bundle to the next and ultimately the observed network morphology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, thin films of metallic Li 2 Mo 6 Se 6 nanowire ropes can be used as a chemical sensor. Xiubin et al 24,25 have showed that resistance of such a thin film changes upon adsorption of organic molecules, suggesting that the electrical conductance of the Mo 6 Se 6 nanowire may change with the type and number of adsorbed atoms or molecules.…”
Section: Introductionmentioning
confidence: 99%